Effects of inclination angle and confining pressure on triaxial unloading-induced slip behaviors of shale fractures - Liu, Yi; Li, Zihan; Zhao, Shisen; Jiang, Jian; Yuan, Chao (Frontiers in Earth Science, 2024)
To explore the effects of fracture inclination angle θ and confining pressure σ 3t on the slip behaviors and friction properties of fractures, the triaxial unloading-induced slip experiments were performed on the shale fractures. The results show that the σ 3t controls the slip modes of fractures, while the θ affects the occurrence of the stick-slip events during the quasi-static slip stage. With the increase in σ 3t , the main slip modes of fracture transform from the stable-slip to stick-slip, and eventually to the creep-slip. The increase in θ facilitated the occurrence of stick-slip events. As the θ increased from 30° to 50°, the number of stick-slip events increased from 0 to 3 and from 2 to 4 for σ 3t = 10 MPa and 20 MPa, respectively. For σ 3t = 40 MPa, no stick-slip event occurred in the slipping process. The θ and σ 3t have great effects on interaction modes between asperities, which directly affected the friction properties of fractures. With increasing σ 3t , the void spaces between the asperities were further compacted, resulting in the transition of asperity interaction from overriding mode to shear-off mode. The transition of asperity interaction model therefore brought about the weakening of friction coefficient at the activation point and the onset of dynamic slip stage. There is a competitive relationship between the θ and σ 3t for the evolution of the friction properties of fractures. As the θ increase from 30° to 50°, for σ 3t = 10 MPa, the mean sheared-off thickness decreased from 0.502 mm to 0.433 mm, while for σ 3t = 40 MPa, the mean sheared-off thickness decreased from 0.505 mm to 0.319 mm. With the increment of θ, the anisotropy of JRC was weakened. We suggested that by adjusting the fracturing angle of hydro-fracturing, the earthquakes with large seismic moments may be effectively mitigated.